The pitch: Some face-to-face minutes to build trust - Fabien Guimtrandy; Thierry Burger-Helmchen (Administrative Sciences, 2022)
The pitch is an important part of the entrepreneur-investor relationship. To come to an agreement, entrepreneurs and investors need to trust each other. However, how does trust arise between them, and how does trust evolve during the few minutes of a pitch? With the aim to develop propositions, we build on previous studies in entrepreneurship and venture funding. Therefore, we rely on the main concepts of trust useful to analyze the interpersonal relationship during a pitch: behavioral trust and transformative trust. We discuss the place of formal documents diffused prior to the pitch and the importance of the oral presentation. We conclude by suggesting testable proposition on the evolution of trust during the pitch.
Keywords: 350; entrepreneurship; angel investors; venturing; business plan; trust; entrepreneurial funding pitch; emotions